2012
DOI: 10.17705/1cais.03109
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitous Healthcare Information System: Toward Crossing the Security Chasm

Abstract: Ubiquitous healthcare information system is increasingly seen as a viable option for reducing the inherent time lag and inaccuracies in the traditional model of healthcare and promoting the delivery and practice of evidence-based healthcare-as and when needed-without any location and time constraints. Although promising, the realization of ubiquitous healthcare information system brings several threats and risks rooted in real-time collection, analysis, storage, transmission, and access of critical medical dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 69 publications
(79 reference statements)
0
2
0
Order By: Relevance
“…Cluster 2b, encompassing nine publications, was derived from the observation that studies within the organizational level concentrated strongly on HIS use and maintenance and the consequences of HIS research. Herein, a vast array of topics was observed, such as the potential for cost reduction through HIS (Byrd & Byrd, 2009), the impact of HIS on product and process innovation in European hospitals (Arvanitis & Loukis, 2014), and the perceived effectiveness of security risk management in healthcare (Zafar et al, 2012). Moreover, we found that practice-oriented methods, such as mixed-method approaches, surveys, data analyses, and case studies, are used predominantly within this cluster.…”
Section: Phase 2: Definition Of Research Objectives and Solution Spacementioning
confidence: 85%
See 1 more Smart Citation
“…Cluster 2b, encompassing nine publications, was derived from the observation that studies within the organizational level concentrated strongly on HIS use and maintenance and the consequences of HIS research. Herein, a vast array of topics was observed, such as the potential for cost reduction through HIS (Byrd & Byrd, 2009), the impact of HIS on product and process innovation in European hospitals (Arvanitis & Loukis, 2014), and the perceived effectiveness of security risk management in healthcare (Zafar et al, 2012). Moreover, we found that practice-oriented methods, such as mixed-method approaches, surveys, data analyses, and case studies, are used predominantly within this cluster.…”
Section: Phase 2: Definition Of Research Objectives and Solution Spacementioning
confidence: 85%
“…Apart from these clusters, quite a few research articles refer to the infrastructure level of observation, addressing information sharing in general (Li et al, 2008), electronic medical records (George & Kohnke, 2018;Wessel et al, 2017), and security and privacy issues (Zafar & Sneha, 2012).…”
Section: Phase 1: Problem Identification and Research Issuesmentioning
confidence: 99%